Fast detection of unique genomic regions - Beatriz Vieira Mourato; Bernhard Haubold (Computational and Structural Biotechnology Journal)
Unique genomic regions are of particular interest in two scenarios: When extracted from a single mammalian target genome, they are highly enriched for developmental genes. When extracted from target genomes compared to closely related neighbor genomes, they are highly enriched for diagnostic markers. Despite their biological importance and potential economic value, unique regions remain difficult to detect from whole genome sequences. In this review we survey three efficient programs for the detection of unique regions at scale, genmap, macle, and fur. We explain these programs and demonstrate their application by analyzing simulated and real data. Example scripts for searching for unique regions are available from the Github repository evolbioinf/sure as part of a detailed tutorial.